Comparison of pharmacokinetics of phytoecdysones and triterpenoid saponins of monomer, crude and processed Radix Achyranthis Bidentatae by UHPLC-MS/MS. (2nd June 2020) - Yang, Liu; Jiang, Hai; Yan, Meiling; Xing, Xudong; Guo, Xinyue; Man, Wenjing; Hou, Ajiao; Yang, Bingyou; Wang, Qiuhong; Kuang, Haixue
Abstract: 1. The aim of this study was to develop a selective, rapid, accurate and sensitive ultrahigh performance liquid chromatography tandem mass spectrometry (UHPLC-MS/MS) method for pharmacokinetic (PK) studies of phytoecdysones and triterpenoid saponins after oral administration of five monomers, crude, wine-processed and salt-processed Radix Achyranthis bidentatae (RAB). 2. A Thermo Hypersil GOLD C18 column (100 mm × 2.1 mm, 1.9 μm) coupled with a mobile phase of (A) acetonitrile and (B) water (both containing 0.3% acetic acid) was used for sample separation. The mass analysis was performed in a triple quadruple mass spectrometer using selected reaction monitoring (SRM) with negative scan mode. 3. The results showed that this method exhibited desirable sensitivity, precision, stability and repeatability. The extraction recoveries of the compounds ranged from 94.2 to 99.8% and the matrix effects ranged from 93.3 to 100.5%. Comparing the C max and AUC of five analytes in those groups showed this tendency: salt-processed RAB > wine-processed RAB > crude RAB > monomer group. The results confirmed the feasibility of TCM theory to enhance the efficacy of processed RAB.